1995
DOI: 10.2307/1941986
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Concentrations in Growth Rings of Taxodium Distichum in a Saltwater‐Intruded Estuary

Abstract: Element analysis by proton induced X‐ray emission spectroscopy was performed on growth rings of baldcypress (Taxodium distichum) growing within the Cape Fear River estuary, North Carolina, USA. Trees from estuarine reaches heavily intruded by saltwater flooding contained larger concentrations of chloride, bromide, and sodium than did trees from less intruded reaches. At three intruded sites, trees nearest open water contained larger concentrations of these elements within outermost sapwood rings than did trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 20 publications
1
30
1
1
Order By: Relevance
“…The results of this study taken together with previous work by Latimer et al (1996) and Yanosky et al (1995) suggest that bald cypress trees do possess the ability to preserve a record of some changes in chemical influxes to the environment, but translocation across multi-decadal sapwood intervals must be considered possible for most of the elements reported above. The longevity and unique ecological niche bald cypress have in wetlands make them worthy of additional study, particularly in environments where a historical record of contamination can be documented.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The results of this study taken together with previous work by Latimer et al (1996) and Yanosky et al (1995) suggest that bald cypress trees do possess the ability to preserve a record of some changes in chemical influxes to the environment, but translocation across multi-decadal sapwood intervals must be considered possible for most of the elements reported above. The longevity and unique ecological niche bald cypress have in wetlands make them worthy of additional study, particularly in environments where a historical record of contamination can be documented.…”
Section: Discussionsupporting
confidence: 72%
“…Yanosky et al (1995) interpreted the heartwood radial translocation of chloride in bald cypress tree rings as a method of disposing of excessive chloride concentrations during seawater intrusion into a North Carolina estuary.…”
Section: Radial Translocation To the Heartwoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather extensive reviews can be found in several chapters of Jacoby and Hornbeck (1987). Dendrogeomorphology has been used in a wide range Xuvial applications, including Xoods (Sigafoos 1964, Yanosky 1982, Hupp 1988, Xoodplain deposition (Sigafoos 1964, Hupp 1988, Hupp and Bazemore 1993, channel dynamics (Hupp 1992, Friedman et al 1996, Scott et al 1997, lake shoreline dynamics (Begin and Filion 1995), saltwater intrusion along streams (Yanosky et al 1995), and mountain glacier activity and debris Xows (Sigafoos andHendricks 1961, Hupp et al 1987). Standard dendrochronological techniques that incorporate ring-width measurement to interpret geomorphic processes may be quite useful.…”
Section: Dendrogeomorphology In Fluvial Systemsmentioning
confidence: 99%
“…4 Altas concentrações de Cl, Br e Na foram encontradas em árvores que se desenvolveram próximas a um estuário marinho e esses resul- tados foram apontados como a causa da diminuição no crescimento normal das plantas. 5 Uma variação anormal nas concentrações de Ca em função do tempo foi verificada em pinheiros siberianos, devido à perturbação de processos de troca iônica causada por íons poluentes na raiz da planta. 6 Um estudo similar foi realizado em florestas do noroeste dos EUA e sua conclusão foi de que há uma intensa correlação entre a ocorrência de chuva ácida e concentrações alteradas de Ca.…”
Section: Introductionunclassified